Promouvoir l’agriculture dans le projet de territoire pour faciliter la mise à disposition du foncier : le cas de la châtaigneraie ardéchoise - Camille Demené; Odile Audibert (VertigO, 2017)
Faced with growing land scarcity, making agricultural land available remains a complex issue. The rural lease contract, created in France during post-war agriculture modernization policies, remains an essential tool for that. Designed to fulfill the requirements of farming modernization and intensification, this contract is however often rejected by landowners, afraid of losing their free will about their property. This paper questions the legitimacy of this type of contract in the current context, towards new modalities or arrangements for making land available. We postulate that developing a territorial agricultural project, shared both by farmers and landowners, stimulates the latter to make their land available for farming. Such project may actually contribute to a better recognition of main issues at stake and to a better acceptance of contract’s terms and conditions. We illustrate our paper with the case of a program conducted in Ardèche (France) to promote renovation of old chestnut’s orchards. We underline especially the importance of constructing this shared project at different scales, from the territory to the agricultural plot, to improve acceptance and conditions of land availability.